Developing an indicator framework for assessing sustainable tourism: Evidence from a Taiwan ecological resort - Tsung Hung Lee; Fen-Hauh Jan; Jui-Tu Liu (Ecological Indicators, 2021)
Scientific understanding of the sustainability indicators of existing nature-based tourism businesses is limited. This study aims to explore a sustainability indicator framework, evaluate the indicator weights and assess performance using a case of a forest ecological resort through three studies. Study 1 explores sustainability indicators for ecological resorts, study 2 calculates the relative weights of each sustainability indicator, and study 3 evaluates the sustainability performance of a forest ecological resort. The analysis revealed 89 indicators classified into six categories: environmental managements, economic management, socio-cultural management, science and technology, human resource management, and government policy. The weights of each indicator were calculated via the analytic hierarchy process with 21 participants. At the first level, the weight of environmental management (0.362) was higher than the weights of the other dimensions (range: 0.192–0.097). The resort’s performance was assessed in terms of importance and performance. The present study’s findings effectively develop a sustainability indicator framework for assessing sustainable tourism that provides valuable theoretical and managerial references, extends our knowledge of sustainable resort development and significantly contributes to the literature.